Pendidikan Berbasis Komunitas dalam Pembentukan Karakter Religius Anak: Studi pada Dasa Wisma Desa Leppe Kecamatan Soropia Kabupaten Konawe - Hilda, Andi; Supriyanto, Supriyanto; Pairin, Pairin (Shautut Tarbiyah-IAIN Kendari, 2025)
This study aims to analyze the contribution of Dasawisma (a community-based women's group) in shaping the religious character of children in Leppe Village, Soropia District, Konawe Regency. The primary focus is to identify the active role of Dasawisma in instilling religious values through family-based religious and social activities, as well as to explore internal and external factors that influence the development of children's religious character. Internal aspects include parenting patterns and parental role modeling, while external aspects involve the social environment and the influence of digital media. This research employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. Data analysis and validity are reinforced through source, technique, and time triangulation. The findings reveal that Dasawisma activities, such as the "My Home is the First Madrasa" program, "One Day One Verse" initiative, and majelis taklim (religious gatherings), are effective in nurturing mothers as exemplary figures and primary educators within the family. Children demonstrated positive development in religious behavior, social ethics, and emotional balance. Key success factors include: (1) the pivotal role of mothers as role models in the household, (2) the habituation of family routines based on Islamic values, and (3) social support and cohesion within Dasawisma. Despite challenges such as parental busyness and digital media influence, the synergy between family and the Dasawisma community plays a vital role in the sustainable development of children's religious character. This integrated approach can serve as a model for strengthening community-based religious character education for children.